Exonuclease mutations in DNA polymerase epsilon reveal replication strand specific mutation patterns and human origins of replication - Shinbrot, Eve; Henninger, Erin E.; Weinhold, Nils; Covington, Kyle R.; Göksenin, A. Yasemin; Schultz, Nikolaus; Chao, Hsu; Doddapaneni, HarshaVardhan; Muzny, Donna M.; Gibbs, Richard A.; Sander, Chris; Pursell, Zachary F.; et al. (Genome Research, 2014)
Tumors with somatic mutations in the proofreading exonuclease domain of DNA polymerase epsilon (POLE-exo*) exhibit a novel mutator phenotype, with markedly elevated TCT→TAT and TCG→TTG mutations and overall mutation frequencies often exceeding 100 mutations/Mb. Here, we identify POLE-exo* tumors in numerous cancers and classify them into two groups, A and B, according to their mutational properties. Group A mutants are found only in POLE, whereas Group B mutants are found in POLE and POLD1 and appear to be nonfunctional. In Group A, cell-free polymerase assays confirm that mutations in the exonuclease domain result in high mutation frequencies with a preference for C→A mutation. We describe the patterns of amino acid substitutions caused by POLE-exo* and compare them to other tumor types. The nucleotide preference of POLE-exo* leads to increased frequencies of recurrent nonsense mutations in key tumor suppressors such as TP53, ATM, and PIK3R1. We further demonstrate that strand-specific mutation patterns arise from some of these POLE-exo* mutants during genome duplication. This is the first direct proof of leading strand-specific replication by human POLE, which has only been demonstrated in yeast so far. Taken together, the extremely high mutation frequency and strand specificity of mutations provide a unique identifier of eukaryotic origins of replication.
10.1101/gr.174789.114